Enabling Successful Migration for Youth in Addis Ababa - Carson, Sarah D. (Tufts Archival Research Center, 2019)
Submitted in partial fulfillment of the degree Master of Arts at the Fletcher School of Law and Diplomacy. This Capstone project is a policy paper for Save the Children examining the meaning of "success" for Ethiopian youth who have migrated to Addis Ababa from rural areas of the country. The findings are based on a mixed methods study conducted in Addis Ababa during the summer of 2018.